Current status of art mobilization in Myeloma - Sevindik, Omur Gokmen; Korkmaz, Serdal; Altuntas, Fevzi (Pergamon-Elsevier Science Ltd, 2017)
Multiple myeloma is the leading indication of autologous hematopoietic cell transplantation (AHCT) worldwide. Hematopoietic progenitor cell mobilization (HPCM) is the first step of a successful AHCT. A minimum of 2 x 10(6) CD34(+) cells/kg are needed for successful engraftment. Growth factors have been used both alone or in combination with chemotherapy for HPCM of patients with myeloma. Mobilization failures result in delays in AHCT and increased cost and resource utility. Strategies to mobilize progenitor cells were mainly chemotherapy and growth factor or growth factor-only mobilization until the advent of plerixafor. Plerixafor is successfully integrated into both growth factor-only and cyclophosphamide and growth factor mobilization strategies with significantly reducing the mobilization failure rate in myeloma patients. The best strategy to mobilize progenitor cells with the highest yield and lowest toxicity and cost in patients with multiple myeloma has not yet been determined. This review aims to summarize the current status of art mobilization in myeloma comparing the pros and cons of different mobilization strategies. (C) 2017 Published by Elsevier Ltd.
Keywords: Hematopoietic cell transplantation; Hematopoietic progenitor cell mobilization; Multiple myeloma